Relative age effects in Korean football: Analysis of age-specific international teams - Jeong, T.-S.; Bang, S.-Y.; Park, S.; Lee, Y.-S.; Kim, Y.-R.; Kim, Y.-S. (The Korean Journal of Sports Medicine, 2019)
Purpose: This study aimed to identify relative age effects of South Korea national male football teams that participated in 38 international competitions in age-specific categories from 2000 to 2018; U-16 (n=176), U-17 (n=82), U-19 (n=198), U-20 (n=147), and U-23 (n=166). Methods: Available information on birth-dates, heights, and body weights of South Korean elite male football players was collected from the official websites. Chi-square test was conducted and odds ratios were calculated with 95% confidence interval in order to examine differences of quarter distribution between expected and observed subgroups. Results: The birth distributions observed in each team were significantly different than those expected in general population of the same age (U-16: Chi2=59.364, p<0.05; U-17:Chi2=36.829, p<0.05; U-19: Chi2=51.697, p<0.05; U-20: Chi2=39.531, p<0.05) except U-23 (Chi2=17.759, p=0.087). The magnitude of birth distribution was 3.2 times higher in the first quarter compared to that in the fourth quarter and was decreased in accordance with age. In accordance with age, the distribution of "competition age group" was significantly decreased in each team (U-16, 91%; U-17, 89%; U-19, 76%; U-20, 63%; U-23, 42%; p<0.05) but that of "under-competition age group" was increased (U-16, 9%; U-17, 11%; U-19, 24%; U-20, 37%; U-23, 58%; p<0.05). There is also significant difference in distribution between both "competition" and "under-competition age group" at the same tournament category (p<0.05). Conclusion: Conclusively, these findings indicate that Korean players who are in the early stage of development have higher "relative age effects" than those in the late stage of development. This may implicate that it is necessary to develop strategies for relatively late-mature players who have potentials in terms of skills and intelligence of football.